2019
DOI: 10.1088/1748-0221/14/09/p09022
|View full text |Cite
|
Sign up to set email alerts
|

Fast component re-emission in Xe-doped liquid argon

Abstract: A: We present the first direct experimental confirmation of the fast component re-emission in liquid argon (LAr) doped with xenon (Xe). This effect was studied at various Xe concentrations up to ∼3000 ppm. The rate constant of energy transfer for the fast component was quantified. It was shown that LAr doped with a high concentration of Xe without TPB has a better PSD efficiency than pure LAr or Xe-doped LAr with TPB. The stability of LAr+Xe mixture was tested for the first time at high Xe concentration for lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 34 publications
(134 reference statements)
9
33
0
Order By: Relevance
“…5. The waveform distortion is consistent with results in the literatures [17,18,20]. The first hump is caused by the scintillation of argon and the second hump is the consequence of argon excimers transferring to xenon excimers.…”
Section: Average Waveform Shapessupporting
confidence: 90%
“…5. The waveform distortion is consistent with results in the literatures [17,18,20]. The first hump is caused by the scintillation of argon and the second hump is the consequence of argon excimers transferring to xenon excimers.…”
Section: Average Waveform Shapessupporting
confidence: 90%
“…This wavelength is significantly more accessible to conventional photosensors than 128 nm. Akimov et al [83] showed that LAr doped with even higher concentrations of Xe, and without TPB, has a better PSD efficiency than pure LAr or Xe-doped LAr with TPB. This implied that the singlet (short-lived) Ar excitation is transferred to Xe as well, and a mechanism assuming an emission of 128 nm photon, subsequently absorbed by Xe, was proposed.…”
Section: Xenonmentioning
confidence: 99%
“…Adding small amounts of xenon to LAr overcomes these limitations. Xenon-doped liquid argon (XeDLAr) features a longer emission wavelength, higher photoelectron yield 𝑌 , shorter effective triplet lifetime 𝜏 3 and longer effective attenuation length 𝜆 att than pure LAr [8,18,[21][22][23]. The increase in photoelectron yield is partly due to the increase in photodetection efficiency with increasing wavelength.…”
Section: Introductionmentioning
confidence: 99%